2022
DOI: 10.1088/2050-6120/aca880
|View full text |Cite
|
Sign up to set email alerts
|

MINFLUX imaging of a bacterial molecular machine at nanometer resolution

Abstract: The resolution achievable with the established super-resolution fluorescence nanoscopy methods, such as STORM or STED, is in general not sufficient to resolve protein complexes or even individual proteins. Recently, minimal photon flux (MINFLUX) nanoscopy has been introduced that combines the strengths of STED and STORM nanoscopy and can achieve a localization precision of less than 5 nm. We established a generally applicable workflow for MINFLUX imaging and applied it for the first time to a bacterial molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…STED microscopy and SIM were used to visualize the Yersinia enterocolitica T3SS pore complex proteins YopB and YopD (uni- With an isotropic localization precision of ~5 nm, these experiments could reproduce the size of the YscL structure determined by Cryo ET to be ~16 nm in diameter (Carsten et al, 2022;Berger et al, 2021). 3D MINFLUX experiments performed in whole bacteria showed that the YscL complexes localized almost exclusively at the plasma membrane and at very low distances to each other (down to ~10 nm apart; Figure 2d; Carsten et al, 2022).…”
Section: Fluore Scen Ce S Rm In S Ecre Ti On Sys Temsmentioning
confidence: 99%
See 3 more Smart Citations
“…STED microscopy and SIM were used to visualize the Yersinia enterocolitica T3SS pore complex proteins YopB and YopD (uni- With an isotropic localization precision of ~5 nm, these experiments could reproduce the size of the YscL structure determined by Cryo ET to be ~16 nm in diameter (Carsten et al, 2022;Berger et al, 2021). 3D MINFLUX experiments performed in whole bacteria showed that the YscL complexes localized almost exclusively at the plasma membrane and at very low distances to each other (down to ~10 nm apart; Figure 2d; Carsten et al, 2022).…”
Section: Fluore Scen Ce S Rm In S Ecre Ti On Sys Temsmentioning
confidence: 99%
“…The z‐ axis is color coded. The white boxed area has a depth of 200 nm along the x‐ axis (Carsten et al., 2022). (e) Trajectories of 3D super‐resolution SMT of eYFP‐labeled Y. enterocolitica T3SS component YscL.…”
Section: Fluorescence Super‐resolution Microscopy Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The secretion apparatus is comprised of a cytosolic platform, an export apparatus, a multi-ring basal body that spans the inner membrane, peptidoglycan layer and outer membrane of bacteria, a hollow needle that is anchored in the membrane through the basal body and extends into the extracellular space, and an oligomeric tip . Proteins required for effector translocation are secreted through the needle and insert into the host membrane to assemble a hetero-oligomeric transmembrane protein complex or translocon. Translocation of effectors into the host cell disrupts cell function and results in a localized disruption of neutrophils. , Inhibition of translocon assembly will prevent effector translocation, protect host cells (mainly neutrophils) from the cytotoxic effect of bacterial effector proteins, and reduce the virulence of the infecting P. aeruginosa strain. Furthermore, since the translocon is assembled and located outside the bacterial cell, , it serves as an ideal target for small-molecule inhibitors.…”
mentioning
confidence: 99%